Cooking Class MP-ASI: Meningkatkan Gizi Anak dan Mencegah Stunting di Kelurahan Kandang Mas Melalui Mentoring Kader dan Ibu - Rismayani; Maulani, Nurul (Gayaku Publisher, 2024)
The role of mothers in preventing stunting is crucial. Therefore, a mother must have extensive knowledge about the nutritional value of food and the preparation of complementary foods for breastfeeding (MP-ASI). Meanwhile, health cadres play a vital role in self-care management of maternal nutrition during pregnancy as an effort to prevent stunting. One of the stunting prevention efforts is through providing nutritious MP-ASI that meets the age requirements of the child. The problem encountered in the Kandang Mas sub-district is that there are still toddlers with weights below the green line, which is a shared responsibility. The purpose of this community service is to maximize the ability of mothers and families in fulfilling children's nutrition. The nutrition education (cooking class) was conducted in December 2023 and was attended by two groups of mothers with infants and toddlers, as well as five posyandu cadres. The methods used included demonstrations, mentoring, and evaluations. The results of this nutrition education were an increase in mothers' knowledge and skills in preparing complementary foods for breastfeeding, enabling mothers of toddlers to practice it at home and enhancing their knowledge to fulfill their role as community mobilizers in preventing and handling stunting. The outcomes of the activity included improved knowledge and skills of mothers in providing children's nutrition and enhanced knowledge and skills of cadres in providing education and mentoring to expectant mothers and mothers of infants/toddlers in their working area. Mothers are expected to apply the knowledge and skills acquired from this activity and share it with other mothers around them. Cadres are expected to apply the knowledge and skills gained to provide education and mentoring to pregnant mothers in their area.